Answer:
Explanation:
AB = a - given
BB₁ is the difference of the diagonal and side of the square with side a:
- BB₁ =
![a√(2) -a=a(√(2)-1)](https://img.qammunity.org/2022/formulas/mathematics/high-school/433yirthw9ad4cb1ojnekq2oik1tqso0ft.png)
Each subsequent line segment is
times the previous.
So we have a GP with the first term of a and common ratio of
.
The sum of the lengths is the sum of infinite GP:
- S = a/(r -1 ), where a - the first term and r - common ratio > 1
So the sum is:
- S = a/(
- 1) = a/
![√(2) =a√(2)/2](https://img.qammunity.org/2022/formulas/mathematics/high-school/8620iadptt20kgs0ctf6e7pi5s032on06p.png)